Peran Pendidikan Islam dalam Membangun Integritas Generasi Muda dan Mencegah Korupsi - Riza, Safrur; Barrulwalidin, Barrulwalidin (Sekolah Tinggi Ilmu Syariah Ummul Ayman Pidie Jaya, 2024)
Corruption has become a scourge that hinders development and the welfare of people in various countries. Efforts to eradicate corruption do not only focus on law enforcement, but also on prevention through anti-corruption education. Anti-corruption education plays an important role in instilling integrity and anti-corruption values from an early age to the younger generation. This article examines the importance of anti-corruption education in a global perspective and Islamic education. Globally, corruption is recognized as a serious issue that has a negative impact on various aspects of life, such as economic, political and social. Anti-corruption education is an important strategy to build a young generation with integrity and anti-corruption. Islamic education has noble values that can be a strong moral foundation for the younger generation to reject corruption. Values such as honesty, justice and responsibility are in line with anti-corruption principles. This article discusses various approaches to anti-corruption education based on Islamic values. These approaches can be implemented through the school curriculum, extracurricular programs, and character building in the family and community. Effective anti-corruption education must be comprehensive and sustainable. It requires cooperation from various parties, such as the government, schools, families, and communities, to build a young generation with integrity and anti-corruption.